2017
DOI: 10.3847/1538-4357/aa91cc
|View full text |Cite
|
Sign up to set email alerts
|

Solar ALMA Observations: Constraining the Chromosphere above Sunspots

Abstract: We present the first high-resolution Atacama Large Millimeter/Submillimeter Array (ALMA) observations of a sunspot at wavelengths of 1.3 mm and 3 mm, obtained during the solar ALMA Science Verification campaign in 2015, and compare them with the predictions of semi-empirical sunspot umbral/penumbral atmosphere models. For the first time millimeter observations of sunspots have resolved umbral/penumbral brightness structure at the chromospheric heights, where the emission at these wavelengths is formed. We find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Whereas the 3 mm holes in the QS seem to be unrelated to the photospheric magnetic field, the 1.25 mm hole presented here is coincidentally hovering above a ∼1.3−1.8 kG magnetic concentration with a field inclination of ∼160−170 • as measured by Hinode. The range in the HMI magnetogram is approximately [−840, 230] G. Interestingly, its brightness temperatures are even lower than the ∼5300 K emission above a sunspot umbra with a magnetic field reaching over ∼2.5 kG (Loukitcheva et al 2017).…”
Section: Overviewmentioning
confidence: 92%
See 1 more Smart Citation
“…Whereas the 3 mm holes in the QS seem to be unrelated to the photospheric magnetic field, the 1.25 mm hole presented here is coincidentally hovering above a ∼1.3−1.8 kG magnetic concentration with a field inclination of ∼160−170 • as measured by Hinode. The range in the HMI magnetogram is approximately [−840, 230] G. Interestingly, its brightness temperatures are even lower than the ∼5300 K emission above a sunspot umbra with a magnetic field reaching over ∼2.5 kG (Loukitcheva et al 2017).…”
Section: Overviewmentioning
confidence: 92%
“…The Atacama Large Millimeter/Submillimeter Array (ALMA, Wootten & Thompson 2009) has overcome the spatial resolution limitations that observing at such long wavelengths entails. ALMA has shown that the landscape of the solar surface at 1 mm is marked by relatively cooler regions such as the QS and sunspot umbras, and hotter features such as plage regions (Loukitcheva et al 2017;Brajša et al 2018), and that the brightness of the mm continuum correlates with that of the Mg ii lines (Bastian et al 2017(Bastian et al , 2018Jafarzadeh et al 2019). However, the large scatter and offset between the two diagnostics is evidence for NLTE effects in the Mg ii lines that make them only partially sensitive to the chromospheric temperatures (e.g., Leenaarts et al 2013a), although there may also be systematic differences in their formation heights (e.g., da Silva Santos et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies that used some of the first solar ALMA observations brought up the need to better understand the formation heights of the ALMA bands in active regions (Loukitcheva et al 2017;da Silva Santos et al 2020;Chintzoglou et al 2020) as they likely differ from the quiet Sun (QS) where the emission is dominated by acoustic shocks (e.g., White et al 2006;Wedemeyer-Böhm et al 2007;Patsourakos et al 2020). Moreover, the contribution functions of the mm continuum may also depend on nonequilibrium ionization/recombination effects in the chromosphere (e.g., Carlsson & Stein 2002;Leenaarts & Wedemeyer-Böhm 2006;Rutten 2017;Martínez-Sykora et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The ALMA dataset we used was provided by the ALMA observatory as part of its Science Verification data release. Previous publications based on this ALMA data release are Bastian et al (2017), Iwai et al (2017), Loukitcheva et al (2017), andShimojo et al (2017). Only Shimojo et al (2017) used data from the same day (2015 December 17) as considered here, and that study was focused on a small brightening rather than the sunspot itself.…”
Section: Observationsmentioning
confidence: 99%